MADRASAH SEBAGAI TIPOLOGI LEMBAGA PENDIDIKAN ISLAM (KAJIAN TENTANG BERBAGAI MODEL MADRASAH UNGGULAN) - Zuhdi, A. (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2012)
â€œMadrasahâ€ is parth of Islamic boarding school to answer various of polemic in the society, especially in Islamic education development, thus Islamic boarding school able to fuse between subject of religion science and common science. Start from that time, Islamic boarding school establish â€œmadrasahâ€ education under its overshide. â€œMadrasahâ€ as institute of Islamic education has blossomed out in a time, as emergence of â€œmadrasahâ€diniyah, â€œmadrasahâ€ of SKB 3 ministers and â€œmadrasah pesantrenâ€. From thatâ€™s models, the great one in development is superior â€œmadrasahâ€. So, unsuprised if there are many schools integrate with Islamic boarding school, thatâ€™s mean in this concerning school which based on Islamic boarding school able to give satisfactions for stakeholder. Moreover, there are many zest from society to educate their child in madrasah wich based on Islamic boarding school. This can be observed based on social changes. As theory from Etzioni, theory of active society that perceived by continuing changes, but still individu who become member of the society.